KEEFEKTIFAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING DENGAN MEDIA GAMBAR SERI TERHADAP KEMAMPUAN MENULIS TEKS EKSPLANASI SISWA KELAS V SD NEGERI BAWANG 02 KABUPATEN BATANG - Kurnia Janatul Ma’wa; Suyitno Suyitno; Diana Endah Handayani (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This research is motivated by the low ability to write explanatory texts of elementary school students, especially in developing ideas, connecting ideas logically, and arranging texts according to structure. Learning that is still teacher-centered causes student engagement to be less than optimal. This study aims to determine the effectiveness of the Problem Based Learning model assisted by a series of pictures on the ability to write explanatory texts of fifth-grade students of SDN Bawang 02, Batang Regency. The study used a quantitative approach with a One Group Pretest-Posttest design on 25 students using a saturated sampling technique. Data collection techniques included tests, observations, and documentation. The validity results showed that the teaching module was valid (95.5%) and the instrument was very valid (99%), while the reliability obtained a Cronbach Alpha value of 0.776. The results showed an increase in the average value from 54.88 to 78.36 and classical learning completeness from 8% to 92%. The hypothesis test showed a significance value of 0.000 <0.05 with a calculated t of -12.652 so that H₀ was rejected and Hₐ was accepted. Thus, the Problem-Based Learning model, supported by a series of images, effectively improves students' explanatory text writing skills. It is recommended to use a clearer and more varied series of images and to encourage students to actively participate in discussions and problem-solving. ABSTRAK Penelitian ini dilatarbelakangi rendahnya kemampuan menulis teks eksplanasi siswa sekolah dasar, terutama dalam mengembangkan ide, menghubungkan gagasan secara logis, dan menyusun teks sesuai struktur. Pembelajaran yang masih berpusat pada guru menyebabkan keterlibatan siswa kurang optimal. Penelitian ini bertujuan mengetahui efektivitas model Problem Based Learning berbantuan media gambar seri terhadap kemampuan menulis teks eksplanasi siswa kelas V SD Negeri Bawang 02 Kabupaten Batang. Penelitian menggunakan pendekatan kuantitatif dengan desain One Group Pretest-Posttest pada 25 siswa menggunakan teknik sampling jenuh. Teknik pengumpulan data meliputi tes, observasi, dan dokumentasi. Hasil validitas menunjukkan modul ajar valid (95,5%) dan instrumen sangat valid (99%), sedangkan reliabilitas memperoleh nilai Cronbach Alpha sebesar 0,776. Hasil penelitian menunjukkan peningkatan nilai rata-rata dari 54,88 menjadi 78,36 serta ketuntasan belajar klasikal dari 8% menjadi 92%. Uji hipotesis menunjukkan nilai signifikansi 0,000 < 0,05 dengan t hitung 18,619 sehingga H₀ ditolak dan Hₐ diterima. Dengan demikian, model Problem Based Learning berbantuan media gambar seri efektif meningkatkan kemampuan menulis teks eksplanasi siswa. Disarankan penggunaan gambar seri yang lebih jelas dan variatif serta pembiasaan siswa untuk aktif dalam diskusi dan pemecahan masalah.